Portuguese and spanish teletandem: the role of mediators - Ramos, Karin Adriane Henschel Pobbe; Carvalho, Kelly Cristiane Henschel Pobbe de (Colombian Applied Linguistics Journal, 2018)
Teletandem is a virtual context of learning languages based on principles of autonomy and reciprocity in which two peers collaborate to learn the language of each other. Usually, the interactions occur in institutional groups mediated by a professor or a graduate student. This paper aims to describe the role of a mediator and the process of mediation in Portuguese and Spanish Teletandem. Previous studies have analyzed how the Teletandem practice in the context of very close languages, such as Portuguese and Spanish, presents some inherent specificity related to the natural possibility of certain intercommunication between the interactants (Ramos, Carvalho, & Messias, 2013; Silva-Oyama, 2010). In this case, it is necessary to observe the process of mediation more closely and consider the relevance of cultural and linguistic aspects. The theoretical assumptions that guide our description and discussion are based on sociocultural theory for second language learning and assume that the learning process happens through interactions between people and the environment in a cooperative manner (Vygotsky, 1978). The methodological perspective that anchors this study is grounded theory (Charmaz, 2006), which is based on a systematic collection of data that, after analysis, originate concepts. The reflection corroborates the fact that the development of the process depends on the involvement of the mediator in different roles and suggests that the principles of autonomy and reciprocity are directly related to the mediation process and can contribute to an effective collaborative context of language learning.